Novel Glial Cell Functions: Extensive Potency, Stem Cell-Like Properties, and Participation in Regeneration and Transdifferentiation - Milichko, Valentin; Dyachuk, Vyacheslav (Frontiers in Cell and Developmental Biology, 2020)
Glial cells are the most abundant cells in both the peripheral and central nervous systems. During the past decade, a subpopulation of immature peripheral glial cells, namely, embryonic Schwann cell-precursors, have been found to perform important functions related to development. These cells have properties resembling those of the neural crest and, depending on their location in the body, can transform into several different cell types in peripheral tissues, including autonomic neurons. This review describes the multipotent properties of Schwann cell-precursors and their importance, together with innervation, during early development. The heterogeneity of Schwann cells, as revealed using single-cell transcriptomics, raises a question on whether some glial cells in the adult peripheral nervous system retain their stem cell-like properties. We also discuss how a deeper insight into the biology of both embryonic and adult Schwann cells might lead to an effective treatment of the damage of both neural and non-neural tissues, including the damage caused by neurodegenerative diseases. Furthermore, understanding the potential involvement of Schwann cells in the regulation of tumor development may reveal novel targets for cancer treatment.